SerpinB3 Upregulates Low-Density Lipoprotein Receptor-Related Protein (LRP) Family Members, Leading to Wnt Signaling Activation and Increased Cell Survival and Invasiveness - Santina Quarta; Andrea Cappon; Cristian Turato; Mariagrazia Ruvoletto; Stefania Cannito; Gianmarco Villano; Alessandra Biasiolo; Maristella Maggi; Francesca Protopapa; Loris Bertazza; Silvano Fasolato; Maurizio Parola; et al. (Biology, 2023)
Abnormal activation of the Wnt-β-catenin signaling cascade is involved in tumor growth and dissemination. SerpinB3 has been shown to induce β-catenin, and both molecules are overexpressed in tumors, particularly in those with poor prognoses. The aim of this study was to evaluate the ability of SerpinB3 to modulate the Wnt pathway in liver cancer and in monocytic cells, the main type of inflammatory cells in the tumor microenvironment. The Wnt cascade, Wnt co-receptors, and low-density lipoprotein receptor-related protein (LRP) members were analyzed in different cell lines and human monocytes in the presence or absence of SerpinB3. The Wnt-β-catenin axis was also evaluated in liver tumors induced in mice with different extents of SeprinB3 expression. In monocytic cells, SerpinB3 induced a significant upregulation of Wnt-1/7, nuclear β-catenin, and c-Myc, which are associated with increased cell lifespan and proliferation. In liver tumors in mice, the expression of β-catenin was significantly correlated with the presence of SerpinB3. In hepatoma cells, Wnt co-receptors LRP-5/6 and LRP-1, implicated in cell survival and invasiveness, were upregulated by SerpinB3. The LRP pan-inhibitor RAP not only induced a decrease in LRP expression, but also a dose–dependent reduction in SerpinB3-induced invasiveness. In conclusion, SerpinB3 determines the activation of the Wnt canonical pathway and cell invasiveness through the upregulation of LRP family members.